(untitled) (Journal of Pedagogical Inventions and Practices, 2026)
This article analyzes the professional qualities required of future teachers of the subject “Tarbiya”. The study is based on a conceptual-analytical research design and uses theoretical analysis, comparative interpretation and structural synthesis. The article identifies value-civic, ethical-pedagogical, communicative-conflictological, didactic-methodological, socio-emotional and reflexive-digital qualities as essential components of the professional profile of a future “Tarbiya” teacher. It is argued that the professional maturity of a future teacher of this subject is expressed not only in subject knowledge, but also in the ability to transform educational values into pedagogical interaction, constructive communication and socially meaningful educational practice